GENDER DIFFERENCES IN THE RELATIONSHIP BETWEEN ANXIETY, SELF-EFFICACY AND STUDENTS LEARNING OUTCOMES ON CHEMISTRY SUBJECT - Siti Amaliyah; Siti Suryaningsih; Luki Yunita (EDUSAINS, 2021)
PERBEDAAN GENDER DALAM HUBUNGAN ANTARA KECEMASAN, EFIKASI DIRI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIAAbstractLearning outcomes of male and female students have different results. Psychological factors in chemistry subjects including anxiety and self-efficacy as factors related to each other. The purpose of this study was to determine the relationship of anxiety and self-efficacy of the chemistry learning outcomes of class X science students related to gender in two public high schools in South Tangerang city for the academic year of 2017/2018. This is a correlational study using a quantitative approach. The population in this study involved 300 students selected through a purposive sampling method which resulted in 161 students relevant to this study including 87 females and 74 males students. The instruments used in the study were anxiety questionnaires and self-efficacy questionnaires with 30 items on each questionnaire, and also for collecting learning outcomes data middle test scores. The results showed the value of sig. 0,00 <α (0,025) which of H0 is rejected and H1 is accepted. The coefficient of determination (R2) shows the percentage contribution of influence on male 26.11% and female 37.08% which can be concluded that there is a relationship between anxiety and self-efficacy towards learning outcomes of chemistry male students have a smaller contribution than female students. Replication of the study in different science disciplines and comparing science and non-science majors are also recommended.AbstrakHasil belajar siswa laki-laki dan siswa perempuan mempunyai perbedaan capaian hasil akhir.  Pada pelajaran kimia faktor psikologi meliputi kecemasan dan self-efficacy menjadi faktor yang berhubungan satu dengan yang lain. Tujuan penelitian ini untuk mengetahui hubungan kecemasan dan self-efficacy terhadap hasil belajar kimia siswa kelas X IPA berkaitan dengan perbedaan gender pada dua sekolah Sekolah Menengah Atas Negeri di Tangerang Selatan tahun ajaran 2017/2018. Penelitian ini merupakan penelitian korelasional dengan pendekatan kuantitatif. Populasi berjumlah 300 siswa dengan penarikan sampel purposive sampling sejumlah 161 siswa meliputi 87 siswa perempuan dan 74 siswa laki-laki. Instrumen yang digunakan berupa angket kecemasan dan self-efficacy sejumlah 30 butir pernyataan pada masing-masing angket serta data hasil belajar berupa nilai Ujian Tengah Semester. Hasil penelitian menunjukkan nilai sig. 0,00 < α (0,025) dimana H0 ditolak dan H1 diterima. Koefisien determinasi (R2) menunjukkan presentase kontribusi pada hubungan yang disumbangan secara simultan pada siswa laki-laki lebih kecil sebesar 26,11% dari siswa perempuan sebesar 37,08% sehingga secara keseluruhan dapat disimpulkan bahwa hubungan antara kecemasan dan self-efficacy terhadap hasil belajar kimia pada siswa laki-laki mempunyai sumbangan lebih kecil dari siswa perempuan dengan capaian hasil belajar yang lebih tinggi. Replikasi studi dalam disiplin ilmu yang berbeda dan membandingkan jurusan sains dan non-sains juga dianjurkan.